2022
DOI: 10.3390/agriculture12091305
|View full text |Cite
|
Sign up to set email alerts
|

Maturity Classification of “Hupingzao” Jujubes with an Imbalanced Dataset Based on Improved MobileNet V2

Abstract: Fruits with various maturity levels coexist among the harvested jujubes, and have different tastes and uses. Manual grading has a low efficiency and a strong subjectivity. The number of “Hupingzao” jujubes between different maturity levels is unbalanced, which affects the performance of the classifier. To solve the above issue, the class balance loss (CB) was used to improve the MobileNet V2 network, and a transfer learning strategy was used to train the model. The model was optimized based on the selection of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Mobile phones, laptops, and desktop computers may all access the Internet with the Jetson Nano [50][51][52]. Mobile Nets are built on a simplified design that creates lightweight deep neural networks using depth-wise separable convolutions [56][57][58][59][60][61][62][63]. In comparison to MobileNetV1, MobileNetV2 makes improvements to achieve higher accuracy with less input parameters and calculations [30,[56][57][58][59][60][61][62][63].…”
Section: Suggestive Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mobile phones, laptops, and desktop computers may all access the Internet with the Jetson Nano [50][51][52]. Mobile Nets are built on a simplified design that creates lightweight deep neural networks using depth-wise separable convolutions [56][57][58][59][60][61][62][63]. In comparison to MobileNetV1, MobileNetV2 makes improvements to achieve higher accuracy with less input parameters and calculations [30,[56][57][58][59][60][61][62][63].…”
Section: Suggestive Methodsmentioning
confidence: 99%
“…Mobile Nets are built on a simplified design that creates lightweight deep neural networks using depth-wise separable convolutions [56][57][58][59][60][61][62][63]. In comparison to MobileNetV1, MobileNetV2 makes improvements to achieve higher accuracy with less input parameters and calculations [30,[56][57][58][59][60][61][62][63]. Using depth-wise separable convolutions with linear bottlenecks and inverted residual blocks (shortcut connections between bottlenecks) we primarily introduce the key features of MobileNetV2, optimize the loss function, and use the improved model architecture from the Face Net model to illustrate MobileNetV2 [62].…”
Section: Suggestive Methodsmentioning
confidence: 99%
“…5 shows the process of identifying and processing data. MobileNetV2 [37][38][39][40][41][42][43] improves over MobileNetV1 [26,44] to gain higher accuracy with fewer parameters and fewer calculations. In this section, we mainly introduce the core features of the MobileNetV2 to be used, the optimization of the loss function and utilizes the improved model architecture from FaceNet model.…”
Section: B Data Processingmentioning
confidence: 99%
“…It has high nutritional value and medicinal value, and is one of the most popular fruits for consumers (Wang et al, 2022). The maturity and moisture content directly affect the taste and fruit quality of jujube (Fu et al, 2021;Sun et al, 2022;Wang et al, 2020), therefore, the researches on jujube maturity and moisture content detection have important significance. Many researchers have studied the detection methods of moisture content and maturity of jujube by selecting appropriate input data and building suitable predictive models.…”
Section: Introductionmentioning
confidence: 99%
“…Mahmood et al (2022) successfully divided jujubes into three categories (unripe, ripe, and over-ripe) based on the convolutional neural network (CNN) according to maturity, which provided theoretical support for the automatic classification system of jujube. Sun et al (2022) used the class balance loss (CB) to improve the MobileNetV2 network, and used A transfer learning strategy to train the model. The results showed that the CB-MobileNet V2 model improved the performance of jujube maturity classification.…”
Section: Introductionmentioning
confidence: 99%